Measuring the Role of Observable Variables of Student Engagement on College Belongingness Using the MIMIC Model - Mardhiyah, Sayang Ajeng; Rachmawati, Rachmawati; Arslan, Gökmen; Iswari, Rosada Dwi (Gadjah Mada Journal of Psychology (GamaJoP), 2025)
Online learning due to social restrictions that occurred during the COVID-19 pandemic reduced student engagement in both academic and non-academic fields, which was followed by a decline in college belongingness. However, student engagement takes various forms. Therefore, this research aimed to look at the role of student engagement in the form of attendance or visits, time spent on campus (duration), and involvement in organizations or activities on campus (covariate variables) on college belongingness (latent variable). The research participants were 400 students from a state university in South Sumatra who were selected using the following inclusion criteria: undergraduates, actively enrolled on campus, being at least a freshman (semester 1), at least 18 years old, and studying at the main campus of the university. Participants were selected using a non-probability sampling technique, namely convenience sampling. Data analysis was done using structural modeling, which was the MIMIC model. The results showed that the frequency of attendance and involvement in organizations or activities has a significant role in the social acceptance dimension of college belongingness, but not the amount of time spent on campus. Apart from that, the three covariate variables have no role in the social exclusion dimension of college belongingness.